The Effect of the Use of Paylater Services on Consumption Patterns Mediated by Personal Money Management in Generation Z with Socioeconomic Factors as Control Variables - Novarianty, Terisha Andra; Hidayat, Agus Maolana; Kartawinata, Budi Rustandi (Asian Journal of Management Analytics, 2025)
This study aims to analyze the influence of the use of paylater services on the consumption patterns of Generation Z with personal money management as a mediating variable and socioeconomic factors as a control variable. Using a quantitative approach, data was collected through questionnaires from 275 respondents, with 200 test-worthy data analyzed using the Structural Equation Modeling (SEM) method through SmartPLS. The results of the study show that the use of paylater services has a positive effect on consumption patterns, and this influence is significantly mediated by personal money management. Socioeconomic factors also affect consumption behavior. These findings support the advancement of financial literacy and risk management among Generation Z in the context of the digital age.